Membangun Harmoni Masyarakat Multikultural melalui Nilai Islam: Integrasi Ukhuwah, Toleransi, dan Karakteristik Islam Indonesia dalam Berbagai Lingkungan Sosial - Bina Prima Panggayuh; Luthfiyah Ananta Asmadi; Ana Mulyana; Lintang Akbari Afsyal; Novita Maulia Harliyani; Adia Safitri (Advances In Education Journal, 2025)
The problem addressed in this study is how humans can live harmoniously in multicultural societies while maintaining civilizational values, with Islam as a source of inspiration. This study aims to analyze the relationship between humans, multicultural societies, and civilization, compare the concepts of Ukhuwah Islamiyah and Ukhuwah Insaniyah, and identify tolerance within religious diversity. The research employed a qualitative literature review method, analyzing Islamic, social, and educational sources. The findings reveal that the concepts of Ukhuwah Islamiyah and Ukhuwah Insaniyah complement each other in fostering brotherhood among individuals and communities. Tolerance within religious diversity can be achieved through the application of moderate Islamic values and the characteristics of Indonesian Islam. Furthermore, multicultural values are significantly manifested in educational settings, family life, and the workplace